Perbedaan Harga Bagi Pelanggan Member dan Non Member dalam Tinjauan Fikih Muamalah (Studi Kasus di Toko Sentral Herbal dan Madu Makassar) - Laode Muhammad Hisyam; Khaerul Aqbar; Muhammad Harsya Bachtiar (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
This research aims to find out how muamalah jurisprudence reviews the price differences for member and non-member customers. The method used is a qualitative research method, using field research with data collection through observation, interviews and documentation. The research approach used is normative descriptive. Based on a review of muamalah jurisprudence, the price difference for member and non-member customers at the Makassar herbal and honey central shop is permitted because it does not contain salt and is not detrimental to customers because there are no requirements in the form of membership fees for member customers. Customers who wish to register as members are required to fulfill the minimum purchase that has been set by the shop so that the contract that occurs is the Ta'līq al-Hibah bi Syarṭ contract (Grant with conditions). Discounts given to member customers fall into the category of grant promises that must be fulfilled by the shop. This aims to ensure that consumers do not experience losses. Price differences that occur between customers do not contain unjust elements. Because in muama fiqh the seller is given the freedom to determine the price offered to the consumer. So that the price that occurs in an agreement or agreement between the seller and the buyer means that one of the principles in buying and selling is fulfilled, namely the principle of satisfaction which makes the sale and purchase valid.